Ammonium Sensing Patch with Ultrawide Linear Range and Eliminated Interference for Universal Body Fluids Analysis - Mingli Huang; Xiaohao Ma; Zongze Wu; Jirong Li; Yuqing Shi; Teng Yang; Jiarun Xu; Shuhan Wang; Kongpeng Lv; Yuanjing Lin (Nano-Micro Letters)
Highlights The as-prepared sensors can detect NH4 + in the body fluids with a high sensitivity of 58.7 mV decade−1 and an ultrawide detection range of 1–100 mM. The biocompatible sensors exhibit desirable biocompatibility and minimal toxicity for continuous and long-term monitoring. The average detection error of the integrated and wireless biosensing patch was 13.2%, and body fluid detection accuracy is improved by more than 18% after cross-calibration.